KChIP2 genotype dependence of transient outward current (Ito) properties in cardiomyocytes isolated from male and female mice. - Lara Waldschmidt; Vera Junkereit; Robert Bähring (PLoS ONE)
The transient outward current (Ito) in cardiomyocytes is largely mediated by Kv4 channels associated with Kv Channel Interacting Protein 2 (KChIP2). A knockout model has documented the critical role of KChIP2 in Ito expression. The present study was conducted to characterize in both sexes the dependence of Ito properties, including current magnitude, inactivation kinetics, recovery from inactivation and voltage dependence of inactivation, on the number of functional KChIP2 alleles. For this purpose we performed whole-cell patch-clamp experiments on isolated left ventricular cardiomyocytes from male and female mice which had different KChIP2 genotypes; i.e., wild-type (KChIP2+/+), heterozygous knockout (KChIP2+/-) or complete knockout of KChIP2 (KChIP2-/-). We found in both sexes a KChIP2 gene dosage effect (i.e., a proportionality between number of alleles and phenotype) on Ito magnitude, however, concerning other Ito properties, KChIP2+/- resembled KChIP2+/+. Only in the total absence of KChIP2 (KChIP2-/-) we observed a slowing of Ito kinetics, a slowing of recovery from inactivation and a negative shift of a portion of the voltage dependence of inactivation. In a minor fraction of KChIP2-/- myocytes Ito was completely lost. The distinct KChIP2 genotype dependences of Ito magnitude and inactivation kinetics, respectively, seen in cardiomyocytes were reproduced with two-electrode voltage-clamp experiments on Xenopus oocytes expressing Kv4.2 and different amounts of KChIP2. Our results corroborate the critical role of KChIP2 in controlling Ito properties. They demonstrate that the Kv4.2/KChIP2 interaction in cardiomyocytes is highly dynamic, with a clear KChIP2 gene dosage effect on Kv4 channel surface expression but not on inactivation gating.